Terrorism as Self-Help: Accounts of Palestinian Youth Incarcerated in Israeli Prisons for Security Violations - Berḳo, ʿAnat (Journal of contemporary criminal justice, 2017)
Adopting and expanding Black’s conception of terrorism as self-help, this study examines how Palestinian youth become involved in security violations. Based on an analysis of in-depth interviews conducted with 10 Palestinian youth incarcerated in Israeli prisons, their experiences are described, including the aftermath of arrest and imprisonment. Their accounts are complemented by interviews with six wardens and correctional officers overseeing the prison’s youth wings, a review of military court transcripts from proceedings leading up to the youth’s incarceration, and observations of participants’ daily prison routines. The data detail pathways and recruitment processes, motivations, rewarding aspects of participation, and the costs incurred as a result by participants and their families. Security violations are analyzed as self-help responses to collective grievances and personal problems. The theoretical and policy implications of the findings are discussed.